Humoral Alloimmunity in Transplantation: Relevance of HLA Epitope Antigenicity and Immunogenicity - Duquesnoy, Rene J. (Frontiers in Immunology, 2011)
HLA mismatching is an important risk factor for antibody-mediated rejection and transplant failure. With the realization HLA antibodies recognize epitopes rather than antigens, it has become apparent that donor-recipient compatibility should be assessed at the epitope level. Recent developments have increased our understanding of the structural basis of HLA antigenicity, i.e. the reactivity with specific antibody and, immunogenicity, i.e. the ability to induce an antibody response. HLAMatchmaker is a computer algorithm that considers each HLA antigen as a series of small configurations of polymorphic residues referred to as eplets as essential components of HLA epitopes. This article addresses the relevance of determining epitope-specificities of HLA antibodies in the identification of acceptable mismatches for sensitized patients considered for transplantation. Permissible mismatching for non-sensitized patients aimed to prevent or reduce HLA antibody responses could consider epitope loads of mismatched antigens and the recently developed nonself-self paradigm of epitope immunogenicity.